EVALUASI SISTEM PENYIMPANAN OBAT DI UPT INTALASI FARMASI KABUPATEN BANJARMASIN - Mochammad Maulidie Alfiannor Saputera; Anna Khumaira Sari; Novia Ariani (Jurnal Insan Farmasi Indonesia, 2022)
Storage drug system is safe, quality, useful and affordable health supplies for the community to ensure the implementation of health development in order to improve the health status as high as possible. The purpose of this study was to determine whether the storage of drugs at the UPT of the Pharmacy Installation of Banjarmasin City was in accordance with the standards of Pharmaceutical Management Training Materials at the Regency Pharmacy Installations, the Directorate of Public Drug Development and Health Supplies, the Directorate General of Pharmaceutical and Medical Device Development, Ministry of Health RI in collaboration with (JICA) The year 2010. This type of research is non-experimental with prospective data collection. The time of this research was carried out in April-May 2019. The population in this study were all drug storage rooms at the UPT Pharmacy Installation of Banjarmasin City, recording and reporting in the April-May 2019 period. The sampling technique used was the saturated sampling technique. Collecting data using direct observation sheet method. The results show that the preparation of storage facilities is 90% appropriate, the spatial arrangement is 90% appropriate, the preparation of drug stock is 75% appropriate and the observation of drug quality is 66% according to standard.